Adapting international social responsibility experience to Ukrainian content - Golovko , Olena; Oriekhova , Kateryna (FINANCIAL AND CREDIT SYSTEMS: PROSPECTS FOR DEVELOPMENT, 2024)
In the conditions of martial law, business activities directly impact the reputation of the company, as well as consumer and public attitudes. Corporate social responsibility is crucial for economic stability, job preservation, and ensuring budget revenues. Studying and disseminating the experience of Ukrainian companies’ social responsibility during the war is necessary to solidify practical experience and ensure their impact on the economy and society in the future. Purpose, objectives and research methods. The aim of the research is to study and promote the experience of corporate social responsibility of Ukrainian companies during martial law, as well as to formulate recommendations for consolidating best practices in the future. The subject of the research is corporate social responsibility in wartime conditions, specifically of Ukrainian companies, and their impact on society and the state. The research employs critical analysis of existing concepts and definitions of corporate social responsibility, comparative analysis of international social responsibility models (American, European, Japanese), as well as in-depth analysis of practical examples from international companies. The information base of the research includes scientific papers, statistical data, and practical examples of social responsibility implementation by well-known companies. Research results. Corporate social responsibility is becoming a key element not only for enhancing corporate capitalization but also for global socio-economic development. The social responsibility models in the USA, Europe, and Japan demonstrate different approaches: individual, collective, and intra-family. The American model emphasizes personal philanthropy, the European model focuses on state regulation and income redistribution, while the Japanese model highlights corporate collectivism and employee social protection. The practical value of the results lies in the fact that analyzing different models of social responsibility allows for adapting these practices to Ukrainian realities. Practical recommendations for integrating elements of international experience can help Ukrainian companies enhance their social responsibility and positively impact the economic and social development of the country. The conclusions drawn can be used to develop a national model of social responsibility, taking into account international experience and the specifics of the Ukrainian economy. This includes state propaganda, local budget involvement, tax incentives, and mandatory social reporting.